HUBUNGAN PENDAPATAN DAN KEAMANAN LINGKUNGAN DENGAN PEMBANGUNAN LINGKUNGAN HIDUP NAGARI DI MINANGKABAU (JURNAL SPASIAL, 2017)
The purpose of this study is to reveal the relationship of income and environmental security with the development of nagari environment in Minangkabau. This type of quantitative research using a relational approach. The location of the research is in five nagari representing Minangkabau area, namely: Nagari Pariangan, Nagari Sungai Antuan, Nagari Sikucur, Nagari Barung Barung Balantai Selatan and Nagari Paru. The results of the study were: 1). The relationship between income and environmental security with the development of the nagari environment is 0.748, this shows a strong relationship, 2). The simultaneous contribution is  x 100% = 56.0%, while the remaining 44.0% is determined by other variables, and 3). The probability value (sig F change) = 0,000 <α 0.05, simultaneously and significantly the income and the environmental security with the development of the nagari environment are related.Keywords: Revenue, Security, Development, Environment